Abdominal Tuberculosis in a Child Presenting with Radiological Evidence of Pneumatosis Intestinalis and Portal Venous Gas (Journal of Health, Population and Nutrition, 2010)
Pneumatosis intestinalis, in association with portal venous gas, is a rare finding in children and young adults. In radiological studies, it is characterized by gas-filled cysts within the bowel-wall. It is often a sign of the serious significant underlying illness and is associated with a poor prognosis. A case of pneumatosis intestinalis and portal venous gas associated with abdominal tuberculosis in a child is presented here. Despite responding well to anti-tubercular treatment, he died suddenly at home, two months after discharge. It is recommended that cases with pneumatosis intestinalis should be carefully observed, although symptoms appear to be improving.Key words: Case studies; Child; Pneumatosis intestinalis; Tuberculosis, Abdominal; TurkeyDOI: 10.3329/jhpn.v28i6.6612J HEALTH POPUL NUTR 2010 Dec;28(6):628-632